Effectivity Comparison of Black Rice Extract and Red Rice Extract Induced on Lipid Profile Changes in Wistar rats (Rattus novergicus - Herlambang, Hendra A.; Kapantow, Nova H.; Kawengian, Shirley E. S. (Jurnal Ilmu dan Teknologi Pangan, 2015)
The objectives of this studies to compare the effectiveness of black rice extract and red rice extract on lipid profile in Wistar rats (Rattus novergicus). This study used a randomized experimental design with pre-post test. The total samples rats were 6 for each experimental group. The treatment group consisted of 4 groups : black rice extract group once a day induced (A) and 3 times a day induced (B) and then red rice extract once a day induced (C) and 3 times a day induced (D). The control group consisted of placebo group (E) and the standard group (F) which was given with Lovastatin. Baseline, Pre and Post data gathering (P1, P2, P3) using random phlebotomy from one rat in each group. Lipid profile measurement results obtained will be analyzed with pre post test in each group and to analyze the differences between groups were tested by using analysis of variance (ANOVA), accompanied by advanced test (post hoc).This research has conclusion that black rice extract or red rice extract effects on lipid profile in which black rice extract has reduced levels of total cholesterol, triglycerides, and LDL and increased HDL levels in Wistar rats (Rattus novergicus) while the extract of red rice reducing levels of total cholesterol, triglycerides, and LDL in Wistar rats (Rattus novergicus). Lovastatin induces lowering LDL levels in Wistar rats (Rattus novergicus). The effectiveness of black rice extract effect is not unlike red rice extract effect in reducing total cholesterol and triglycerides in Wistar rats (Rattus novergicus). Keywords : black rice, effectivity, red rice, lipid profile